Artificial Intelligence: A Clarification of Misconceptions, Myths and Desired Status - Emmert-Streib, Frank; Yli-Harja, Olli; Dehmer, Matthias (Frontiers in Artificial Intelligence, 2020)
The field artificial intelligence (AI) has been founded over 65 years ago. Starting with great hopes and ambitious goals the field progressed though various stages of popularity and received recently a revival in the form of deep neural networks. Some problems of AI are that so far neither 'intelligence' nor the goals of AI are formally defined causing confusion when comparing AI to other fields. In this paper, we present a perspective on the desired and current status of AI in relation to machine learning and statistics and clarify common misconceptions and myths. Our discussion is intended to uncurtain the veil of vagueness surrounding AI to see its true countenance.